2020
DOI: 10.1108/jmp-09-2018-0420
|View full text |Cite
|
Sign up to set email alerts
|

Agree to disagree: Examining the psychometrics of cybervetting

Abstract: PurposeDue to the paucity of research on web-based job applicant screening (i.e. cybervetting), the purpose of the current study was to examine the psychometric properties of cybervetting, including an examination of the impact of adding structure to the rating process.Design/methodology/approachUsing a mixed-factorial design, 122 supervisors conducted cybervetting evaluations of applicant personality, cognitive ability, written communication skills, professionalism, and overall suitability. Cross-method agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…Despite the emphasis placed by various authors on the need to structure the process of gathering applicant information via social networks, the study of Schroeder et al (2020) found that adding structure to the process did not lead to the expected improvements in psychometric properties demonstrated in social media screening. In reaction to these findings, Schroeder et al (2020) presume that structuring methods other than those used in their study may be more effective. As a result, future research on the effectiveness of different methods of stucturing the process of social media screening may provide further insights for practitioners.…”
Section: Consistencymentioning
confidence: 88%
See 4 more Smart Citations
“…Despite the emphasis placed by various authors on the need to structure the process of gathering applicant information via social networks, the study of Schroeder et al (2020) found that adding structure to the process did not lead to the expected improvements in psychometric properties demonstrated in social media screening. In reaction to these findings, Schroeder et al (2020) presume that structuring methods other than those used in their study may be more effective. As a result, future research on the effectiveness of different methods of stucturing the process of social media screening may provide further insights for practitioners.…”
Section: Consistencymentioning
confidence: 88%
“…The practice of social media screening in selection raises data accuracy concerns in several ways: In their study, Schroeder et al (2020) demonstrate that the assessments of applicants based on information from social media screening were generally inconsistent with the information provided by the applicants. Regarding the quality and reliability of social media information, Davis (2007) has identified the problem of inaccurate or false information about candidates, especially beyond their own control, as being one of the most serious issues in social media screening.…”
Section: Accuracymentioning
confidence: 97%
See 3 more Smart Citations